2003
DOI: 10.1097/00042737-200311000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of systemic glucocorticoid therapy on bone metabolism and the osteoprotegerin system in patients with active Crohn's disease

Abstract: A decrease in bone mineral density in patients with Crohn's disease appears to result, at least in part, from a short-term effect of systemic glucocorticoid. Modulation of osteoclastogenesis by the receptor activator of NF-kappaB ligand/osteoprotegerin cytokine system and decreased osteoblastic function may be the underlying molecular basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 34 publications
2
19
0
2
Order By: Relevance
“…Furthermore, we also noted a trend towards lower bone mass in children with CD compared to UC. The differences in bone mass between CD and UC patients have been described previously [27,28]. Malnutrition was significant in the IBD group, especially in CD patients.…”
Section: Discussionsupporting
confidence: 63%
“…Furthermore, we also noted a trend towards lower bone mass in children with CD compared to UC. The differences in bone mass between CD and UC patients have been described previously [27,28]. Malnutrition was significant in the IBD group, especially in CD patients.…”
Section: Discussionsupporting
confidence: 63%
“…In patients with renal disease, a decrease in both OPG and OC serum circulating levels was shown, with a parallel increase in bone resorption markers during the first two weeks of GCs treatment (13). In addition, during a 3-month period of high-dose GC treatment (60 mg prednisolone per day), it was observed that OPG decreased after 2 weeks and returned to baseline after 3 months, while soluble RANKL serum levels increased (30). In contrast, considering CS, in three studies, OPG serum levels were found to be higher in patients compared to healthy controls (14,31,32).…”
Section: Discussionmentioning
confidence: 96%
“…This enhanced bone resorption activity is not anymore balanced by the osteoblast bone formation activity, causing a loss in bone mass and a progressive destruction of bone microarchitecture. Induced androgen and estrogen deficiency, systemic glucocorticoid exposure (22), T cell activation as in rheumatoid arthritis and skeletal malignancies (23,24) also enhance the release of RANKL, ending up in promoting osteoclastogenesis and inducing unbalanced bone loss. Denosumab is a fully human monoclonal antibody that binds with high affinity and high specificity to RANKL, thereby preventing RANKL from binding to RANK (25).…”
Section: Pharmacological Approach To Osteoporosismentioning
confidence: 99%